The Jokowi Effect on the Victory of Prabowo: Do People Vote for Continuity? - Putra, Cakra Yudi; Febriani, Dyah Ayu; Nugroho, Andri Tantyo Cahyo; Dartanto, Teguh (UI Scholars Hub, 2025)
The 2024 Indonesian presidential election marked a striking realignment as Prabowo Subianto—a former opposition leader—secured victory with the tacit endorsement of outgoing President Joko Widodo (Jokowi). This study investigates how the enduring popularity and policy achievements of Jokowi shaped voter preferences in favor of Prabowo, effectively positioning the election as a referendum on political continuity. Building on theories of economic voting and retrospective performance evaluation, the analysis explores the impact of district-level economic indicators, social media penetration, ideological orientation, social assistance distribution, and sociocultural characteristics on electoral outcomes. Employing Ordinary Least Squares (OLS) regression on data from 481 administrative regions, the study uncovers a robust positive relationship between the 2019 vote share for Jokowi and the 2024 performance of Prabowo. These findings highlight the potency of pocketbook voting—voter assessments of their economic welfare—in sustaining incumbent influence and advancing the theory of economic voting by demonstrating how the legacy of a sitting president can persist through perceptions of economic stewardship.